National Trends in Atrial Fibrillation Hospitalization, Readmission, and Mortality for Medicare Beneficiaries, 1999–2013. Issue 13 (28th March 2017) - Freeman, James V.; Wang, Yun; Akar, Joseph; Desai, Nihar; Krumholz, Harlan
Abstract : Background: Data are lacking on national trends for atrial fibrillation (AF) hospitalization, particularly with regard to long-term outcomes including readmission and mortality. Methods: We studied all Medicare fee-for-service beneficiaries between 1999 and 2013, and we evaluated rates of hospitalization for AF, in-hospital mortality, length of stay, and hospital payments. We then evaluated rates of long-term outcomes, including 30-day readmission, 30-day mortality, and 1-year mortality. To evaluate changes in rates of AF hospitalization and mortality, we used mixed-effects models, adjusting for age, sex, race, and comorbidity. To assess changes in rates of 30-day readmission, we constructed a Cox proportional hazards model adjusting for age, sex, race, and comorbidity. Results: Adjusted rates of hospitalization for AF increased by ≈1% per year between 1999 and 2013, and although geographic variation was present, this trend was consistent nationwide. Median hospital length of stay remained unchanged at 3.0 (interquartile range 2.0–5.0) days, but median Medicare inpatient expenditure per beneficiary increased from 2932 (interquartile range 2232–3870) to 4719 (interquartile range 3124–7209) per stay. During the same period, the rate of inpatient mortality during AF hospitalization decreased by 4% per year, and the rate of 30-day readmission decreased by 1% per year. The rates of 30-day and 1-year mortality decreased more modestly by 0.4% and 0.26% per year, respectively. Conclusions: Between 1999 and 2013, among Medicare fee-for-service beneficiaries, patients were hospitalized more frequently and treated with more costly inpatient therapies such as AF catheter ablation, but this finding was associated with improved outcomes, including lower rates of in-hospital mortality, 30-day readmission, 30-day mortality, and 1-year mortality. Abstract : Supplemental Digital Content is available in the text.